Dr Henryk Jordan’s Park as an example of pioneering physical culture work in Poland - Noga, Robert (Health Promotion & Physical Activity, 2017)
Henryk Jordan – who lived in Cracow at the turn of 19th and 20th century – was a well-known and esteemed medical doctor, social and political activist as well as an art patron and publicist. His most prominent heritage is a city park named after him. At the time it was a location where pioneering work promoting physical culture among youngsters took place. First trainings started in 1889 and instantly became popular. Trainings were carefully organized and combined physical training with a promotion of a patriotism. At the beginning of 1890’s Jordan introduced football which became very popular amongst male teenagers. Football became a part of trainings and competitions, and after a while organized football teams started to play in the park. This was a starting point of the oldest still existing Polish football clubs: Cracovia and Wisła. Jordan’s ideas inspired others, and soon many other cities in Poland. Jordan’s park exists until today, however, it plays a role of a popularizing recreational spot in the city centre. In other cities, so-called “Jordan’s gardens” became playgrounds for children.